The Analysis of Likert Scales Using State Multipoles: An Application of Quantum Methods to Behavioral Sciences Data. (February 2013) - Camparo, James; Camparo, Lorinda B.
Though ubiquitous, Likert scaling's traditional mode of analysis is often unable to uncover all of the valid information in a data set. Here, the authors discuss a solution to this problem based on methodology developed by quantum physicists: the state multipole method. The authors demonstrate the relative ease and value of this method by examining college students' endorsement of one possible cause of prejudice: segregation. Though the mean level of students' endorsement did not differ among ethnic groups, an examination of state multipoles showed that African Americans had a level of polarization in their endorsement that was not reflected by Hispanics or European Americans. This result could not have been obtained with the traditional approach and demonstrates the new method's utility for social science research.